Calreticulin Negatively Regulates the Surface Expression of Cav1.3 L-Type Calcium Channel - Karnabi, Eddy (2013)
BACKGROUND: The neuroencrine Cav1.3 L-type Ca channels have been recently found in the Human fetal heart and shown to play a vital role in Ca entry from the sarcolemma into the cell and in Ca homeostasis. Calreticulin, a Ca binding endoplasmic reticulum (ER) resident protein, has been recently shown to translocate to the cell surface where it’s role and function are just emerging. Here, we demonstrated a novel mechanism of Cav1.3 and calreticulin interaction resulting in downregulation of Cav1.3 channel densities in native Human fetal cardiac cells and Human Embryonic Kidney cell lines (tsA201). METHODS AND RESULTS: Cell surface and cytoplasmic staining of calreticulin was demonstrated first in cultured human fetal cardiomyocytes (HFC), gestational age 18-24 weeks, using confocal microscopy thereby establishing that calreticulin is present at the cell surface in HFC. Co-immunoprecipitation from HFC using anti-Cav1.3 Ca channel antibody, and probing with anti-calreticulin antibody revealed a 46 kDa band corresponding to calreticulin suggesting that Cav1.3 Ca channel and calreticulin co-assemble in a macromolecular complex. Co-expression of Cav1.3 and calreticulin in tsA201 cells resulted in a decrease in surface expression of Cav1.3 Ca channels. These findings were consistent with the electrophysiological studies showing that co-transfection of Cav1.3 Ca channel and calreticulin resulted in 55% reduction of Cav1.3 Ca current densities recorded from tsA201 cells. CONCLUSIONS: The results show the first evidence that calreticulin: 1) is localized outside the ER on the cell surface of HFC; 2) coimmunoprecipitates with Cav1.3 L-type Ca channel; 3) negatively regulates Cav1.3 surface expression thus resulting in decreased Cav1.3 Ca current densities. The data demonstrate a novel mechanism of modulation of Cav1.3 Ca channel by calreticulin, which may be involved in pathological settings such as autoimmune associated congenital heart block where Cav1.3 Ca channels are downregulated.